Putting violent armed conflict in the center of the Salween hydropower debates - Suhardiman, Diana; Rutherford, J.; Bright, S. J. (Informa UK Limited, 2017)
Regional economic integration has become the dominant development pathway promoted, endorsed, and followed by many developing country governments in South East Asia and globally. Focusing on hydropower development, this article shows how forces of globalization manifested in the Myanmar government’s strategies to promote economic growth are shaping the Salween River basin’s development trajectory. Contesting the general belief that economic development would help the country’s transition to full democracy and achieve peace, it illustrates how hydropower development plans in the basin are closely interlinked with human rights issues. Well known for its long histories of violent conflict involving the Myanmar military and ethnic armed groups in various states, hydropower development in the Salween River is not only linked to the ongoing peace process in Myanmar but could also have direct implications on the actual significance of the process. Despite the signing of nationwide ceasefire agreements in 2012, hydropower dam projects could contribute to and trigger reoccurrences of violent armed conflict. Recognizing this conflict-prone and politically fragile condition as the main characteristics of Salween water governance is essential if we are to strive for sustainable and just development.